PENTINGNYA PROGRAM LEGISLASI DAERAH DALAM PEMBENTUKAN PERATURAN PERUNDANG-UNDANGAN DAERAH DAN PROSPEK PENGATURANNYA - Tekege, Petrus (SKETSA : Jurnal Ilmu-Ilmu Sosial, 2018)
The locale legislation program (the planning of legislation enactment) is an important part in locale legislation enactment. This program will be a guide for locale government and local representative to make a priority scale of locale legislation enactment. Other wise there are judicially problem in this program because there are no clarity about position and mechanism of program’s arrangement and management